Tindak Tutur Direktif dalam Pembelajaran Bahasa Indonesia di SMAN 1 Mijen, Demak - Elok Octaviani Putri; Sri Puji Astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
Directive speech acts in learning Indonesian can be used as a way to determine the success of the learning process that takes place in class X IPA and X IPS at SMAN 1 Mijen, Demak.this study aims to describe the form and role of directive speech acts in learning Indonesian at SMAN 1 Mijen. This study uses the directive act theory of Ibrahim’s opinion. Data collection uses the technique of Simak Bebas Libat Cakap, recording technique and notetaking. The data analysis using a pragmatic equivalent method. The results of this study revealed that (1) the form of directive speech acts of class X IPA found four forms including 'requestives', 'questions', 'requirements', and 'advisories', while class X IPS found six forms including 'requestives', 'questions', 'requirements', 'prohibitive', 'permissives' and 'advisories'; and (2) directive speech acts in Indonesian language learning play a role in providing information, providing direction, disciplining, encouraging students to interact, motivate, and provide advice.